Manajemen Pengaturan Persentase Pemberian Pakan pada Jadwal Waktu Pemberian Makan terhadap Tingkah Laku Makan Ayam Petelur Jantan - T. D. Nova; Y. Heryandi; P. Ilham (Jurnal Peternakan, 2020)
This study aims to determine the timing of proper feeding of male hens and how to eat male hens to meet there daily needs. The feeding behavior parameters observed were screening observations (scores), number of strokes (times/5 minutes), feeding breaks at the time of observation (seconds), and the remaining feed in the drinking water (mg). The results of the variance analysis showed the percentage of feed amounting to the feeding time schedule had a significant effect (P<0.05) on screening results, number of stakes and residual feed in the drinking water but did not significantly (P>0.05) on feeding breaks. The results of the study showed that the screening score of 2.54-2.99, (noise at score skrining (2-3) the number of adlibitum pegs was 428.63 times/5 minuts and the difference in the percentage of administration was 488.24-541.50 times/5 minutes, eating breaks 207.59-235.64 seconds, and the remaining feed in the adlibitum drinking pot 8.32 mg and the results of the difference in the percentage of giving 11.58-17.78 mg. The concluded of the research, that the percentage of the amount of feeding with the time schedule of given affects the behavior of eating male hens. Male hens given adlibitum feed showed calmer eating behavior than chickens fed at percentages and mealtimes.